Fertigation of Plant with IoT Based System forManagement and Monitoring - Muhammad ’Abid Rosdi; Mohd Shamian Zainal (Progress in Engineering Application and Technology, 2024)
An IoT-enabled smart fertigation system integrates sensors like soil, ultrasonic, pH, DHT22, and a Pneumatic Diagraph Water Pump, connected to a NodeMCU ESP32 microcontroller. Real-time data on soil conditions is transmitted to a cloud platform like Blynk for analysis. Advanced algorithms and machine learning provide precise fertilization suggestions, optimizing water and resource use. Thesystem allows remote monitoring and control via smartphones or PCs, promising enhanced crop development, resource efficiency, and farm management.